Whole mitochondrial genome analysis of Tai-Kadai-speaking populations in Southwest China - Feng, Yuhang; Zhang, Hongling; Wang, Qiyan; Jin, Xiaoye; Le, Cuiyun; Liu, Yubo; Wang, Xiaoxue; Jiang, Huang; Ren, Zheng (Frontiers in Ecology and Evolution, 2022)
As a single matrilineal gene, human mitochondrial DNA plays a very important role in the study of population genetics. The whole mitogenome sequences of 287 individuals of the Tai-Kadai-speaking population in Guizhou were obtained. It was discovered that there were 82, 104, and 94 haplotypes in 83 Bouyei individuals, 107 Dong individuals, and 97 Sui individuals, respectively; and the haplotype diversity in Bouyei, Dong, and Sui groups was 1.000±0.02, 0.9993 ±0.0015, and 0.999 ±0.002, respectively. The result of neutrality tests of the Tai-Kadai-speaking population in Guizhou showed significant negative values, and the analysis of mismatch distribution showed an obvious unimodal distribution. The results implied that Guizhou Tai-Kadai-speaking populations had high genetic diversities and may have experienced recent population expansion. In addition, the primary haplogroups of studied populations were M*, F, B, D, and R*, implying that they may origin from Southern China. The matrilineal genetic structure of the Tai-Kadai-speaking populations in Guizhou was analyzed by merging the mitogenome data of 79 worldwide populations as reference data. The results showed that there were close relationships between studied populations and other Tai-Kadai as well as some Austronesian populations in East and Southeast Asia. Overall, the mitogenome data generated in this study will provide important data for the study of genetic structure of Tai-Kadai speaking populations.